Primeros registros de Tersina (Tersina viridis) para la Ecoregión Chaqueña de Argentina - Zelaya, Patricia V.; Salvador, Sergio A.; Giraudo, Hugo; Klavins, Juan (Nuestras Aves, 2013)
Este artículo no cuenta con un resumen.